Modelling of the elementary surface processes occurring in the course of heterogeneous catalytic reactions - Holovko, M.F.; Vakarin, E.V. (Condensed Matter Physics, 2000)
A short review of theoretical results on the Langmuir-Hinschelwood and
Eley-Rideal reaction schemes is presented. It is shown that the rates of elementary processes at the surface are coupled through the bulk properties
of adsorbing species. This concerns the dependence of the chemical potential on the association-dissociation balance and on the adsorbate density near the surface. Adsorption is shown to be sensitive to a mechanism
of dimer adsorption (associative or dissociative). Dissociative adsorption
gives a nonmonotonic behaviour of the coverage with the surface activity.
Simultaneously, the dissociation degree increases with increasing adsorption. The associative adsorption implies the existence of a low-density critical point around which the adsorption isotherms are discontinuous. This
causes an abnormal low surface diffusion at low densities. Implementation
of these results to kinetic properties are brieﬂy discussed. Подано короткий огляд теоретичних результатів для схем реакцій
Лангмюра-Гіншельвуда та Елі-Ріделя. Показано, що ступені елементарних процесів на поверхні є зв’язані через об’ємні властивості адсорбованих компонент. Це пов’язано залежністю між хімічним потенціалом асоціативно-дисоціативного балансу і густиною адсорбату біля поверхні. Показано, що адсорбція є чутливою до механізму
димерної адсорбції (асоціативної або дисоціативної). Дисоціативна
адсорбція веде до немонотонної залежності покриття від поверхневої активності. Одночасно ступінь дисоціації зростає з ростом адсорбції. З асоціативною адсорбцією пов’язана можливість існування в області малих густин критичної точки, в околі якої адсорбційні ізотерми не є неперервними. Це приводить до аномально низької
поверхневої дифузії в області малих густин. Коротко обговорюється
вплив цих результатів на кінетичні властивості.